Effect of dietary supplementation with Vitex negundo L. var. cannabifolia extract on the growth performance, blood chemistry, gut morphology, and gut microbiota of broilers - Huang, Tianqi; Tang, Xinggang; Ye, Qianni; Yuan, Minggui; Zhang, Xiaoai; He, Junheng; Cao, Yali; Hu, Qi; Xiang, Rong (Frontiers in Veterinary Science, 2025)
The aim of this study is to evaluate the effects of Vitex negundo L. var. cannabifolia extract (VNE) on the growth performance, antioxidant status, blood chemistry, and cecal microbiota of broilers. A total of 240 one-day-old partridge broilers in total were randomly assigned to 5 treatment groups of 48 chicks each, which were divided into 6 replicates of 8 chicks. The first group (Control) was given the basal diet (only); the second group (Positive) was given the basal diet with 300 mg/kg of Macleaya cordata extract, and the low-dose group (Low), the middle-dose group (Mid) and the high-dose group (High) were given the basal diet with VNE at a dose of 1.3, 2.6 and 3.9 g/kg diet, respectively. The results showed significant improvements (p < 0.01) in growth performance, with significant improvements in body weight, weight gain, and feed conversion ratio at 3.9 g/kg diet. Broilers in the high-dose VNE group exhibited a significant reduction in serum total cholesterol (TC), alanine aminotransferase (ALT), and albumin (ALB) compared to the control group. Furthermore, this group showed a concurrent increase in immunoglobulins (IgA, IgG, and IgM). Furthermore, the morphology and microbial content of the jejunum and ileum were improved in broilers fed on a diet supplemented with a high dose of VNE compared to the control group. Cecal microbiome analysis showed that VNE addition obviously improved cecal microbial composition, as indicated by the increased relative abundance of Clostridia vadinBB60, the Rikenellaceae Rc9 gut_group, Christensenellaceae_R-7_group, Clostridia UCG-014, and Anaerofilum. In conclusion, dietary supplementation with VNE increased the productive performance, immunity, and blood chemistry profile, while modulating cecal microbiota in broiler chicks.